الكمالية لدى الطلاب المتوفقين وغير المتفوقين بالمرحلة الثانوية بمدينة الرياض - السليمان، نورة إبراهيم (جامعة القصيم, 2016)
هدفت الدراسة إلى التعرف على أبعاد الكمالية والتوصل فيما إذا كان هناك فروق ذات دلالة إحصائية بين متوسطات درجات الطلاب المتفوقين وغير المتفوقين على مقياس أبعاد الكمالية (الاهتمام بعدم الوقوع في الأخطاء، تصور التوقعات للأخرين، تصور النقد من الآخرين، تصور مستوى الأداء الشخصي، تقدير التنظيم) كما هدفت الدراسة إلى التعرف على أثر بعض المتغيرات كالنوع، التخصص، وبعض المتغيرات الأسرية) عدد الإخوة، عدد الأخوات، وترتيب الميلاد) على أبعاد الكمالية لدى الطلاب المتفوقين دراسيا. شمل مجتمع الدراسة الطلاب بالمرحلة الثانوية، تم اختيارهم طبقيا من خمس مناطق تعليمية بمدينة الرياض. تكونت عينة الدراسة النهائية من (297) طالب وطالبة، كان منهم (184) طالب وطالبة من المتفوقين دراسيا، و(113) طالب وطالبة من غير المتفوقين. وتم استخدم مقياس أبعاد الكمالية من إعداد الباحث. وتبين من النتائج أن هناك فروق دالة إحصائيا بين متوسطات درجات الطلاب المتفوقين وغير المتفوقين على أبعاد مقياس الكمالية التالية (التصور لمستوى الأداء الشخصي، وتقدير التنظيم، والتصور لتوقعات الآخرين)، وكانت لصالح الطلاب المتفوقين دراسيا. كما كان هناك فروق دالة إحصائيا بين متوسطات درجات الطلاب المتفوقين وفقا للنوع، والتخصص، وعدد الأخوات في أسرهم. وبناء على نتائج الدراسة قدم الباحث العديد من التوصيات من أهمها إعداد برامج توعوية وإرشادية للمعلمين، وأولياء الأمور، للتعريف بأبعاد الكمالية السلبية والوقاية من آثارها.
This study aimed to identify the dimensions of perfectionism, and find out whether there were significant differences between gifted and non-gifted student on the dimensions of perfectionism scale (concern over mistakes, perception of other's expectation, perception of other's criticism, personal standards, and organization) Also to identify whether there were statistically significant differences between the mean scores of gifted students according to their gender, specialization, as well certain family variables (numbers of sisters, brothers, and birth order).A stratified sampling was used to select ten high schools from five educational regions of Riyadh, Saudi Arabia. the study sample consisted of (297) high school studenta,184 were gifted and, 113 were non-gifted. The Dimensions of perfectionism Scale was used. The study results showed that, there were statistically significant differences between gifted and non-gifted students on the scale dimensions of perfectionism (perception of other's expectation, personal standards, and organization) in favor of gifted students. Also, the results showed that there were significant differences between gifted students on the dimensions of perfectionism scale according to their gender, specialization, and numbers of sisters in their families. Depending on the study results, the researcher have come-up with some recommendations that can help teachers, parents, to be aware of the effects of perfectionism among gifted students, and how to prevent its negative effect.
Keywords: الرياض -- التعليم الثانوي -- التفوق الدراسي -- علم النفس التربوي